How to treat androgenetic alopecia - the most common form of hair loss. A review - Monika Stradczuk; Łukasz Mazurek; Barbara Rękas; Wojciech Mazurek; Mateusz Piętak; Barbara Kruczyk; Wojciech Kopacz; Joanna Olędzka; Zuzanna Czach; Dominika Bachurska (Kazimierz Wielki University, 2024)
Introduction and purpose Androgenetic alopecia (AGA) is one of the most common causes of baldness worldwide. It affects up to 80% of men by the age of 70 and up to 40% of postmenopausal women. In AGA etiology and pathogenesis, the three essential components play a key role - genetic inheritance, patient age and hormonal effects of androgens. In the following review, we have described the available FDA-approved and off-label treatments for AGA, along with their efficacy and potential side effects that should always be considered to prevent treatment discontinuation by the patients. The state of knowledge The pathogenesis of AGA is based on inherited dihydrotestosterone (DHT) sensitivity in the scalp skin, which leads to progressive hair loss. The literature documents the effectiveness of several treatments with different mechanisms of action in AGA therapy, but only topical minoxidil and oral finasteride gained FDA approval so far. Minoxidil acts by the blood vessels dilatation that increases the flow of oxygenated and growth factor-enriched blood to the hair follicles in the skin. 5-alpha reductase inhibitors, such as finasteride and dutasteride are another threapeutic option. Thy act by the inhibition of 5-alpha reductase, the enzyme which converts testosterone to DHT - the main causative agent of androgenetic alopecia. Recently, topical applications of minoxidil and finasterid, along with completely new emerging treatments for androgenetic alopecia are gaining popularity among doctors and patients.  Summary This review describes current treatments for AGA, considering their efficacy, optimal doses, and the most common side effects. An important fact to emphasise is that androgenetic alopecia is based on a genetic predisposition, and treatment requires long-term use. For this reason, when choosing a medication, it is essential to cooperate with the patient and combine different therapeutic methods to achieve the desirable outcome while avoiding adverse reactions.